Indonesian Legal Politics in the Future in Accommodizing the Role of the Army in the Prevention and Eradication of Terrorism - Marwan; Imam Syafei (Journal of Law, Politic and Humanities, 2025)
The purpose of finding Indonesian legal policy in the future in accommodating the role of the military in preventing and eradicating terrorism. This research is a normative legal research, to determine the differences and similarities between the legal systems of one country and another. Comparison of Indonesia and Malaysia. The government and the military are tied by a regulatory knot to build a formal legal basis that regulates the duties and functions of the military in the state system. The TNI is a state apparatus that handles the defense sector and in its implementation is assisted by other components, namely supporting components and reserve components from the people. The direction of Indonesian legal policy in the future in efforts to prevent and eradicate terrorism is indeed a complex problem, therefore multi-party synergy is needed in handling it. In the past era, the TNI carried out duties not only in the defense sector but also in the socio-political sector, so after we entered the reform era, the TNI immediately placed its right position in accordance with the democratic state order. We have left the socio-political role and we only concentrate on the field of defense and state security, in the future it could help maintain public security and order in order to build the duties of the Police. Handling criminal acts of terrorism in Indonesia is part of law enforcement under the authority of law enforcement officers. So that the TNI cannot enter the realm of law enforcement because its main tasks and functions are different. So that the involvement of the TNI in eradicating terrorism as regulated in Article 7 Paragraph (2) and Paragraph (3) of Law Number 34 of 2004 concerning the TNI must be emphasized that the TNI can play a role when a terrorist attack threatens state sovereignty and/or when it is related to military operations and law enforcement officers themselves are no longer able to handle a terrorism problem.